Business-to-customer (B2C) electronic commerce: an implementation process view - Bahari, Mahadi (IEEE, 2016)
In spite of the many studies conducted on B2C e-commerce implementation, prior studies have presumed B2C e-commerce implementation to be a “plug and play” exercise rather than process based. Consequently, many of these initiatives have failed to deliver the benefits expected for e-commerce companies. Therefore, it is now important to revisit the literature in order to understand the process of implementation by exploring the relevant factors for each phase of B2C e-commerce implementation. To locate papers that represent the topic adequately, full-text papers in ABI/INFORM, Elsevier, Emerald and ScieneDirect search archives published between 2006 and 2015 were selected. The keywords employed in the academic search were limited in extent to the title and body text search by selecting keywords, namely, 1) e-commerce implementation and 2) B2C e-commerce implementation. Based on a content analysis of the reviewed literature, this paper has identified 19 (nineteen) factors that contribute to the implementation process of B2C e-commerce systems. All these factors were then mapped into the implementation process which corresponding phases in Kotter's model that were guided by academic literature and organizational success stories (i.e., four case studies that were most relevant to the research context were reviewed). A conceptual framework is then proposed, which contributes to the theoretical understanding of B2C e-commerce implementation process studies.